The Effect Of Uln And Pma On Economic Growth In Indonesia With Labor As a Moderating Variable - Askal Samiudin (Journal of Economic and Business Analysis, 2023)
The purpose of this study is to evaluate the effect of foreign debt and foreign direct in- vestment (FDI) on Indonesia's economic growth for the period 2012-2021, with labor as a moder- ating variable. The research methodology used is quantitative method and the analysis technique used is multiple regression analysis technique. The results showed that partially variable X1 (for- eign debt) had an effect on Indonesia's economic growth, while variable X2 (FDI) had no significant effect. But if tested simultaneously, the two X variables have a significant influence on economic growth in Indonesia.